Pelatihan Ilmu Teknologi Komputer Dalam Meningkatkan Kemampuan Administrasi Perangkat Desa Suka Jaya - Idris, Zulkifli; Syahwami, Syahwami; Rusnaini, Sasmita; Widya Astuti, Ira; Burhanuddin, H.; Ariyanto, Ariyanto; Ernawati, M, (HIMPUNAN DOSEN GEMILANG INDONESIA, 2024)
Abstract - Computer technology information science is a science that is widely used in various fields life, one of which is the use of computer technology to make work easier village officials. However, for a village official, this job is not easy. One of the obstacles is the lack of human resources for village officials to understand existing technology, so they It takes a long time to carry out administrative work. A similar situation exists in Suka Jaya village officials, Rimbo Ulu District, Tebo Regency.